Nanotoxicology and nanotechnology: new findings from the NIEHS and Superfund Research Program scientific community - Carlin, Danielle J. (Reviews on environmental health, 2014)
Nanomaterials are characterized by their small size (i.e., nanometer scale) and can be engineered from nearly any chemical substance, creating materials that differ in composition, particle size, shape, and surface coatings. These materials are often seen as a "double-edged sword" by having properties that make them potentially beneficial in product development, drug delivery, and remediation of hazardous substances, but these same properties may result in interaction with biological systems and potential effects in the environment. The National Institute of Environmental Health Sciences (NIEHS) is interested in both the potential risks associated with exposure to these materials, while harnessing the power of engineered nanomaterials to improve public health. This presentation will consist of discussion of nanoparticle studies by NIEHS researchers and the extramural community and its efforts to develop cross-agency initiatives to solve the many vexing issues associated with nanomaterials. For example, researchers from the NIEHS National Toxicology Program (NTP) are evaluating a number of nanomaterial classes in comprehensive toxicology studies. NIEHS also has an extensive extramural research grant portfolio consisting of the Nano Grand Opportunities (Nano GO) Program and NIEHS Centers for Nanotechnology Health Implications Research (NCNHIR) Consortium consisting of U19 and U01 Cooperative Centers. Furthermore, the NIEHS Superfund Research Program (SRP), which supports a network of university (P42, R01), small business (SBIR/STTR), and training grants (R25), provides funding to grantees evaluating the toxicology of nanomaterials, developing new or improved nanotechnologies to monitor and remediate hazardous substances, and training professionals in the use of these of materials. The NIEHS's Worker Education Branch also offers educational materials for training workers on risks of nanotechnology in laboratories, manufacturing facilities, at hazardous waste cleanup sites, and during emergency responses. In conclusion, this presentation will stimulate dialogue regarding the need for more research on these complex materials and serve as a resource about the wide variety of ongoing studies on nanomaterials at NIEHS that will contribute to the determination of risk associated with this class of compounds.